Improvement of organizational processes: case study Elevaria Café & Tostaduría Company - Suarez Torres, Betty Lizby; Rubio Jimenes, Giuliana Milagros; Valdiviezo Juarez, Nataly Maricel; Granda Pretel, Fatima Alexandra; Alva Medina, Rosa Elvira; Sifuentes Valverde, Carolina Lisbeth; Pomatanta Delgado, Bruno (LACCEI, 2025)
The objective of this research is to propose a model for improving organizational processes in the company Elevaria Café & Tostaduría. The research is descriptive and cross-sectional, and an observation guide was used as instruments to identify the current situation of the company. company. and a questionnaire for the collection of data and information. Previous studies indicate that Human Resources management is becoming a challenge for companies in the coffee sector, even more so when this sector is constantly growing. The case study shows that using business process management (BPM) in the process improvement model could reduce 78% of the execution time and 88% of the operating costs of payroll calculation management. The results show the measurement of the processes as they are executed using the Balanced Scorecard model together with the ACM methodology, the analysis of the results and the proposal of activities for the improvement of prioritized processes such as recruitment and selection of personnel, hiring personnel, training staff, management of absences and dismissal of staff